The flora of south-eastern Mato Grosso State (Brazil): a review of herbarium collections - Erica Campos (Pensoft Publishers, 2021)
The diversity and richness of the Brazilian flora are documented in herbarium collections. When areas are deforested, but not documented, we lose both flora and the opportunity to know which species occupied those areas. The south-eastern mesoregion of Mato Grosso State, comprising 22 municipalities, has undergone the loss of native vegetation cover, accelerated by the substantial expansion of agribusiness. For an in-depth look at the consequences and the current state of the flora in that mesoregion, we consulted both speciesLink and JABOT databases. More specifically, we carried out a comprehensive study of herbarium collections by municipality and compiled data including scientific name, collection date, collection locality, collector name and observations made during collection. We obtained 5,861 records of angiosperms, ferns and lycophytes of 160 families, 770 genera and 1,792 species. The specimens are deposited in 80 herbaria of which the Herbarium of Universidade Federal de Mato Grosso (UFMT) hosts the largest collection. Rondonópolis was the most sampled municipality, whereas 50% of the municipalities were poorly sampled and one showed no collection records at all. Amongst the species occurring only in Mato Grosso, eleven were collected only in that mesoregion and twenty species were under some degree of threat. Our study recommends increasing collection and identification efforts to enable effective conservation actions and improve richness estimates for the State of Mato Grosso and the Cerrado, in general, before more of the flora is lost to deforestation.